HUBUNGAN HASIL BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN PERILAKU SISWA DI SMPN 3 CIHAMPELAS KBB - Hadi Ahmad Bukhori; Ibnu Imam Al Ayyubi; Murharyana (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
The existence of Islamic religious lessons to produce good ethical behavior for students is proposed as a research problem to be applied in learning activities. The purpose of this study was to determine the magnitude of the relationship between PAI learning outcomes and student behavior is significant or not. The approach used is quantitative. The method used is the explanatory method. This method is used to test the relationship or influence between the hypothesized variables. The subjects in this study were all class VIII/C students of SMP Negeri 3 Cihampelas with a total of 41 students as the population and samples were taken using a random sampling technique. The questionnaire given to students consisted of 23 statement items related to Islamic education learning outcomes and 40 statement items related to student behavior. The findings of this study are that there is a relationship between Islamic education learning outcomes and student behavior. This is shown from the results of the comparison of Â and Â namely 0.824 â‰¥ 0.308 with a contribution size of 2.97 in the sufficient category. From this study, it can be concluded that the relationship between Islamic education learning outcomes and student behavior is significant